PERAN AKUNTANSI RUMAH TANGGA DALAM PENGELOLAAN KEUANGAN SYARIAH - Ardiana, Elsa; Muthalib, Ahmad Abdul; Arafah, Muh. (Indonesian Scientific Journal of Islamic Finance, 2024)
Household financial management plays a crucial role in creating socio-economic stability, especially for rural communities such as those in Ulo Village, Tellu Siattingge District. One common approach to support financial management is cash flow recording. However, inadequate recording often makes it difficult for households to monitor and analyze income and expenditure patterns effectively. From a Sharia perspective, proper financial management becomes even more significant as it must align with Sharia principles, such as transparency, fairness, and the prohibition of usury. This study aims to identify the role of household accounting in Sharia-based financial management, including supporting factors, implementation barriers, and solutions to overcome challenges. The research employs a qualitative approach, collecting data through field observations, in-depth interviews, and documentation. The study involves five informants, all of whom are housewives with children and have been married for at least 5 years. Data analysis was conducted thematically using triangulation techniques to ensure result validity. The findings indicate that household accounting plays an essential role in helping families create budgets, record financial transactions, support decision-making, and plan long-term finances. Supporting factors include awareness of the importance of financial recording and basic understanding of Sharia principles, while the main obstacles involve limited knowledge and lack of consistency in recording. Nonetheless, informants reported significant benefits, such as using financial records as a reference for managing finances in the following month. The implementation of simple household accounting has proven effective for housewives in Ulo Village in controlling expenditures, budgeting, and improving financial management in line with Sharia principles. For housewives in similar areas, simple financial recording can be an initial step toward enhancing family economic stability. This study recommends Sharia-based financial literacy training and the development of simple financial recording tools. Future research could explore the long-term impacts and the role of technology in supporting Sharia financial management at the household level..